Faktor yang Mempengaruhi Perubahan Harga Telur di Pasar Tradisional Kabupaten Jember - Shodiqoh, Atik Qotus; Purwandhini, Ari Septianingtyas (KUBIS, 2024)
Eggs have high nutritional value, so they are good for all levels of society, both children and the elderly. Apart from that, the price is quite affordable, which is one of the reasons why eggs are popular with people as a food source. The amount of egg consumption continues to increase. However, demand for eggs remains fluctuating, this is due to several conditions where demand for eggs experiences a decrease or increase. This causes egg prices to fluctuate. So this makes egg farmers anxious because of the uncertainty in egg prices. The aim of the research is to determine the factors that influence the price of eggs in the traditional markets of Jember Regency. The research method uses quantitative descriptive methods and data analysis obtained from BPS and Siskaperbapo. The research results show that (1) Production variables (X1) and demand (X2) both have a significant effect on the price of rice in the traditional market of Jember district. Where the production variables (X1) and demand (X2) both have a significant effect on egg prices. Where Production (X1) has a tcount of -5,810, this value is greater than ttable which is 2,036. For the demand variable (X2) it has a tcount of 5,997, this value is greater than ttable which is 2,036.